Marginal Bone Level and Clinical Parameter Analysis Comparing External Hexagon and Morse Taper Implants: A Systematic Review and Meta-Analysis - Samuele Fuda; Bruno Gomes dos Santos Martins; Filipe Correia de Castro; Artak Heboyan; Sergio Alexandre Gehrke; Juliana Campos Hasse Fernandes; Anna Carolina Volpi Mello-Moura; Gustavo Vicentis Oliveira Fernandes (Diagnostics, 2023)
The goal of this systematic review was to verify the marginal bone loss (MBL) and other clinical parameters comparing external hexagon (EH) and Morse taper (MT) implants when they were evaluated within the same study. The focused question was, “For patients (P) treated with external connection (I) or Morse taper (C) dental implants, were there differences in the marginal bone crest maintenance after at least three months in occlusal function (O)”? As for the inclusion criteria that were considered, they included clinical studies in English that compared the MBL in implants with EH and MT, with follow-up of at least three months, that were published between 2011 and 2022; as for the exclusion criteria, they included publications investigating only one type of connection that analyzed other variables and did not report results for the MBL, reports based on questionnaires, interviews, and case reports/series, systematic reviews, or studies involving patients with a significant health problem (ASA Physical Status 3 and above). The PubMed/MEDLINE, Embase, and Web of Science databases were screened, and all of the data obtained were registered in a spreadsheet (Excel®). The Jadad scale was used to assess the quality of the studies. A total of 110 articles were initially identified; 11 were considered for full-text reading. Then, six articles (four RCTs and two prospective studies) met the eligibility criteria and were included in this study. A total of 185 patients (mean age of 59.71) were observed, and the follow-up ranged from 3 months to 36 months. A total of 541 implants were registered (267 EH and 274 MT). The survival rate ranged between 96% and 100% (the average was 97.82%). The MBL was compared among all periods studied; therefore, the common assessment period was the 12-month follow-up, presenting greater MBL for EH than for MT (p < 0.001). A mean MBL of 0.60 mm (95% CI 0.43–0.78) was found after the same period. BoP was reported in 5 studies and plaque index was reported in 4 (2 with more than 30%). Deep PD was observed in three studies. High heterogeneity was observed (I2 = 85.06%). Thus, within the limitation of this review, it was possible to conclude that there is higher bone loss in EH than in MT implants when evaluating and comparing this variable within the same study. However, the results must be carefully interpreted because of this review’s limited number of clinical studies, the short assessment period, and the high heterogeneity found.